Faktor - Faktor yang Berhubungan dengan Kualitas Rumah Sehat - Purwanto, Medy; Zanariah, Zanariah; Nurasbon, Nurasbon (JURNAL KESEHATAN TERAPAN, 2025)
A proper dwelling should ideally provide comfort, safety, and health support for its occupants to facilitate daily activities and improve overall well-being. A healthy living environment is a crucial factor in enhancing public health quality. The concept of a healthy house encompasses both technical and social aspects in managing risks, including the building's location, structural conditions, functionality, Decent housing should ideally provide a sense of comfort, safety, and support the health of its occupants in order to facilitate daily activities and improve overall well-being. A healthy living environment is a crucial component in efforts to enhance public health status. The concept of a healthy house encompasses both technical and social aspects in managing various risks, including the location of the building, physical structure, function, maintenance, and the surrounding environmental conditions.In addition, elements such as access to clean water, facilities for cooking, washing, food storage, as well as systems for waste and sewage disposal are also important indicators in assessing the feasibility of a healthy house. The objective of this study is to assess the quality of healthy housing in the area. The method used is an analytical survey with a cross-sectional approach. This study was conducted in July 2024 in Sukaraja Village, Suak Tapeh Sub-district, Banyuasin Regency. The study population included all heads of households, with 48 respondents randomly selected. Data were collected using a checklist.Univariate analysis showed that 45.8% of houses were categorized as healthy, with the following breakdown: ceilings meeting the criteria at 37.5%, permanent walls 37.5%, floors 39.6%, openable windows 56.2%, ventilation 45.8%, kitchen smoke disposal facilities 41.7%, and natural lighting 39.6%. There was a significant relationship between these elements and the feasibility of a healthy house.Therefore, health workers are expected to actively provide education and real examples regarding healthy housing standards. The community also needs to understand the criteria for a healthy home before starting construction in order to create a living environment that supports the health of all family members